Balanço de água e sais no solo cultivado com o quiabeiro irrigado sob diferentes lâminas de água salobra - Campos, Marcos de Sousa (2013)
Okra is a vegetable growing in the irrigated areas of the Northeast and knowledge of the water requirements of the crop is of fundamental importance to irrigation management. The aim of this study was to evaluate the evapotranspiration, the crop coefficient (Kc), the production and the balance of water and salts in the soil cultivated with okra irrigated with brackish water at different water depths. Therefore an experiment was conducted at the station lisimétrica Department of Environmental Sciences and Technology of UFESA in Mossoró, RN. We used a completely randomized design and treatments consisted of two irrigation waters, being a low salinity with electrical conductivity (EC = 0.5 dS m-1) as a witness (L0) 105% ETc and other brackish with (EC = 3.5 dS m-1) applied in four different blades L1, L2, L3 and L4 that correspond respectively to 65, 85, 105 and 125% of crop evapotranspiration (ETc) determined as Allen et al. (2006). The ETc lysimeters was measured using the water balance applied to a soil block. The water consumption from 5th week until the end of the cycle in the lysimeter control treatment was 424.54 mm. The estimated by Kcdual for this period was 483.33 mm. The average values of Kc was 0.56, 0.68 and 0.58 L1 and 0.78, 1.15, 0.93 respectively for the L0 in stages II, III and IV. Kc was determined by Kcdual 0.57, 1.27, 1.21 and 0.95 respectively for the phases I, II, III and IV. Significant effects of treatments and sampling times (days after sowing) and interaction for leaf area index. Significant effects of treatments on the production of fresh fruit and number of fruit per plant. The electrical conductivity of the saturation extract of soil increased in all treatments with saline water, similar effect was observed in Cl-, Na+ and sodium adsorption ratio (SAR). Salinity in the soil profile decreased with increasing water depth. The salinity of irrigation water with the blade deficit increased soil salinity and decreased ETc